Gender differences in paid work over time: Developments and challenges in comparative research. - Lena Hipp; Kristin Kelley (PLoS ONE)
This paper examines gender differences in paid work over time and illustrates the pitfalls encountered by any comparative research that only considers either labor force participation rates or average working hours. To do so, we analyze harmonized survey data from Europe and the United States from 1992 to 2022 (N = 43,283,172) and show that more progress was made in closing gender gaps in labor force participation rates than in working hours. In most countries, women's labor force participation rates increased considerably, but their average working hours decreased, whereas both men's labor force participation rates and average working hours decreased or stagnated (but nonetheless still remained much higher than women's). We show and argue that these countervailing trends in working hours and labor force participation rates make it difficult to paint a coherent picture of cross-national differences in women's and men's paid work and of changes over time. In response, we propose "work volume" as a supplementary or alternative measure for any type of comparative research. Work volume records zero working hours for nonemployed individuals and thus allows straightforward comparisons between women's and men's (or any other groups') involvement in paid work. Using the proposed work volume measure, we show that gender gaps in paid work decreased over time, but that even in 2022, men's involvement in paid work remained considerably higher than women's-with gender gaps being lowest in the Scandinavian and the former Communist countries.